Toroidal magnetic field ripple and ion orbit loss effects on edge toroidal rotation in J-TEXT Tokamak plasmas. (4th May 2018) - Zeng, Zhong; Luo, Jian; Zhuang, G.; Gentle, K.; Hu, Q.M.; Cheng, Z.F.; Rao, Bo; Zhang, Zhengqing; Shi, Peng; Chen, Jie; Yu, Q.
Abstract: The edge toroidal rotation on J-TEXT is in the counter-current direction and sensitive to electron density and safety factor. During a density ramp-up phase, the initial toroidal rotation in the edge region (e.g. r/a = 0.7–1), having one speed with little radial dependence, evolves to develop a radial profile when the edge density is sufficiently large. The effects of ripple-induced thermal loss on plasma rotation are predicted by neoclassical theory for those discharges, and comparisons with the measurements are performed. The predictions agree well with the measurements over a range of plasma conditions, confirming that using the ripple effect to interpret the phenomenon is appropriate in certain parameter regimes, while in others the neoclassical effects are not sufficient to predict the experimental observations.